Impact of Chief Executive Officer (CEO) Succession Policy on CEO Turnover Announcement in Malaysia - Shubasini Sivapregasam; Aslam Izah Selamat; Norhuda Abdul Rahim; Junaina Muhammad (Asian Academy of Management Journal of Accounting and Finance, 2020)
This paper presents a fresh perspective on chief executive officer (CEO) turnover, where the impact of CEO turnover on firm value is analysed based on whether the removal is planned or unplanned. A total of 146 announcements for ten years in Malaysia is examined using an event study method. The results indicate that, in general, CEO turnover announcements cause a significant reaction due to changes in the firm’s investment decisions. Specifically, a significant positive impact exists when CEO turnover occurs as planned. In a planned turnover, the negative news of the removal of the CEO is immediately minimised with the positive news of a CEO appointment, indicating the positive impact of establishing a CEO succession plan on firm value. This finding adds new knowledge to the current literature and allows policymakers to examine the establishment of a CEO succession policy.